Recognising the Other in the Face of Abuse in the Church - Martínez, Julio L.; Montero Orphanopoulos, Carolina (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2024)
This article uses the theory of recognition to explore abuse in the Church. Starting from Hegel, it leads to the development of the recognition/contempt pair of Axel Honneth’s neo-Hegelian philosophy. Developing this theory as a frame of reference, the harm perpetrated on victims and survivors of sexual abuse, abuse of power and abuse of conscience in the Catholic Church is reviewed. Furthermore, as an approach to the resolution of the always risky Hegelian struggle for recognition — even more so in the institution that wants to be a sacrament in today’s world — the states of peace proposed by Ricoeur are considered. Through the categories of the exchange of gifts, forgiveness and reparation, Christian faith sets out the path of liberation from sin and evil, without claiming to exert pressure on the responses of the victims. The fullness of forgiveness in Christian theology can be seen in Jesus’ gift of himself to humanity on the cross, which reaches its fullness in the resurrection. This forgiveness is offered to everyone, whatever the evil they have committed, but it requires authenticity in the recognition of guilt, repentance and reparation: reconciliation appears as a horizon where love founded on freedom, truth and justice overcomes evil. We seek to establish a dialogue between leading authors of the philosophy of recognition and Christian theology, without disregarding the contribution of other sciences.
Keywords: recognition; sexual abuse; abuse of conscience and power; gift; gratuitousness; love-justice; forgiveness; reparation; reconciliation